PENGAWASAN OPERASIONAL BUS TRANS METRO OLEH PD PEMBANGUNAN KOTA PEKANBARU - Wulandary, Melisa; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Standard operational procedure becomes the reference for operational oversight Trans Metro Pekanbaru bus, from an operational perspective to maximize service to customers, minimizing violations and maximizing efficiency in order to improve the quality of Trans Metro bus Pekanbaru to society.This study aims to determine whether the operational supervision Trans Metro Pekanbaru bus in accordance with the existing field. This study used a qualitative descriptive method of data collection techniques such as interviews, observation, documents and literature studies.Results of this research is the Trans Metro bus operational control by PD Pembangunan has not gone well because they found employees who lack an understanding of operating standards so that any offense and not the maximum service to the detriment of passengers. PD Pembangunan also respond to any complaints about the public so that such violation becomes protracted.Keywords: Controlling, Standard Operational Procedures, Services